Railroad Vine (Ipomoea pes-caprae): Identification and Uses - Stephen Henry Brown; Marc S. Frank (EDIS)
Railroad vine is one of the most widely distributed beach plants in the world. The moving sand and salt spray make the beach environment a harsh one, and the plants that live there are specialized to colonize this environment. This new 7-page document, published by the UF/IFAS Environmental Horticulture Department, describes railroad vine's leaves, flowers, fruit, planting and maintenance, and insect and disease problems. Written by Stephen H. Brown and Marc S. Frank. https://edis.ifas.ufl.edu/ep587